Plasmonic locator with sub‐diffraction‐limited resolution for continuously accurate positioning. Issue 2 (17th January 2022) - Gao, Peng Fei; Zou, Hong Yan; Gao, Ming Xuan; Li, Yuan Fang; Huang, Cheng Zhi
Abstract: Both the accurate distance measurement and positioning information at the nanoscale are important for the analysis of micro/nano interactions. Plasmon ruler has been an indispensable optical tool to detect the chemical and biological dynamic processes via distance‐dependent plasmon coupling in the nearly aggregated state. But it cannot disclose the detailed and accurate information of positions and dynamic movements of its two plasmonic components owing to the inherent diffraction limit. Herein, a plasmonic locator is presented which consists of a heterotypic pair of red/blue plasmonic components with significant wavelength difference (∼150 nm). Attributed to the detuned energy (∼0.64 eV) of the two components, the plasmonic locator has the ability of sub‐diffraction‐limited resolution (center to center, 30 nm) and accurate positioning under conventional dark‐field microscopy, making the relative dynamic information of nearby red/blue components be recorded accurately at video rate. As an important complement to the current aggregate science and technology of plasmonics, this newly developed plasmonic locator presents a facile means to realize super‐resolution imaging, accurate positioning, and continuous tracing in chemical and biological interactions at the single‐molecule level. Abstract : A plasmonic locator consisting of a heterotypic pair of plasmonic nanoparticles with detuned energy was used for sub‐diffraction limit resolution and accurate positioning under conventional DFM. Plasmonic locator is simple and independent of the anisotropy and wavelength modulation, thus providing a novel strategy for continuous tracing in chemical and biological interactions.